2010
DOI: 10.4028/www.scientific.net/kem.447-448.396
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Molding Testing of the Blazed Gratings for Microoptics Applications

Abstract: This paper presents the experimental investigation of the optimal hot embossing replication to prevent the nanoscale thermal deformation of microstructures replicated from the electroless Ni mold fabricated by the diamond tool-interfered scribing process. The fabricated microstructures have the blazed profile with a period of 2.0 ㎛ and a depth of 0.2 ㎛ and a thermoplastic material PMMA as the replica was used. The hot embossing molding was carried out under the several experimental conditions. In terms of a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…It has been demonstrated that ultra-precision diamond tooling is a suitable technique for processing advanced optical surfaces, 29 31 including the fabrication of free-form blazed gratings 32 34 Xu et al 35 . used ultra-precision diamond tooling to cut a convex reflective variable spacing grating with a blazed structure and a grating density of 300 lines/mm.…”
Section: Grating Fabrication and Replicationmentioning
confidence: 99%
“…It has been demonstrated that ultra-precision diamond tooling is a suitable technique for processing advanced optical surfaces, 29 31 including the fabrication of free-form blazed gratings 32 34 Xu et al 35 . used ultra-precision diamond tooling to cut a convex reflective variable spacing grating with a blazed structure and a grating density of 300 lines/mm.…”
Section: Grating Fabrication and Replicationmentioning
confidence: 99%
“…Using the inexpensive single-point diamond turning (SPDT) method, Advanced Machine and Optical Systems (AMOS) in Belgium showed that freeform gratings (FFG), which are blazed gratings on surfaces with no rotational symmetry, are possible [ 19 ]. High-quality freeform blazed grating elements made with a diamond can even be used instead of electron beam lithography to make holograms [ 55 , 56 ].…”
Section: Fabrication Capability Of Convex Blazed Gratingsmentioning
confidence: 99%
“…Due to the process kinematics it is possible to machine multi focus Fresnel lenses consisting of different segments [2]. Blazed gratings are another application example, which can also be machined with linear process kinematics [3] or by diamond milling [4]. These processes enable the machining of a wide range of structure sizes ranging from few to several hundred micrometers of the groove width and a few hundred nanometers to several micrometers of the groove depth.…”
Section: Introductionmentioning
confidence: 99%